2010
DOI: 10.1590/s1679-87592010000700009
|View full text |Cite
|
Sign up to set email alerts
|

Chronic toxicity test with sea urchin Echinometra lucunter and Lytechinus variegatus (Echinodermata: Echinoidea), exposed to light-stick - flag paternoster used for longline surface fishing

Abstract: In this work, the chronic toxicity of a mixture of light-stick chemicals and water was tested. The light-stick is used in fishery activities to catch swordfish. The tubes were collected on the beaches of the Costa dos Coqueiros -BA, Brazil, in the period from 14th to 31st July 2007. The method used was a short chronic toxicity test where embryos of the sea urchins Echinometra lucunter and Lytechinus variegatus were exposed to a stock solution consisting of the supernatant formed from a mixture of sea water and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Several researchers have extended the widelyused sea urchin fertilization assay (e.g., Environment Canada, 2011 ) to investigate various aspects of early development in echinoderms, including growth rate (e.g., Saco‐Alvarez et al, 2010 ), developmental delay, and morphological abnormalities up to the pluteus larval stage (e.g., Bellas et al, 2005 ; Cesar‐Ribeiro et al, 2010 ; Anselmo et al, 2011 ; Morroni et al, 2016 ; Picone et al, 2016 ). As indicated previously, it has been demonstrated that exposure to T4, T3, or T2 accelerates the initiation of skeletogenesis (spicule formation) in sea urchin Strongylocentrotus purpuratus gastrulae (2 dpf) and in six‐armed pluteus larvae (10–14 dpf; Taylor and Heyland, 2018 ).…”
Section: Evaluation Of Existing Invertebrate Test Methods For Their P...mentioning
confidence: 99%
“…Several researchers have extended the widelyused sea urchin fertilization assay (e.g., Environment Canada, 2011 ) to investigate various aspects of early development in echinoderms, including growth rate (e.g., Saco‐Alvarez et al, 2010 ), developmental delay, and morphological abnormalities up to the pluteus larval stage (e.g., Bellas et al, 2005 ; Cesar‐Ribeiro et al, 2010 ; Anselmo et al, 2011 ; Morroni et al, 2016 ; Picone et al, 2016 ). As indicated previously, it has been demonstrated that exposure to T4, T3, or T2 accelerates the initiation of skeletogenesis (spicule formation) in sea urchin Strongylocentrotus purpuratus gastrulae (2 dpf) and in six‐armed pluteus larvae (10–14 dpf; Taylor and Heyland, 2018 ).…”
Section: Evaluation Of Existing Invertebrate Test Methods For Their P...mentioning
confidence: 99%
“…An average of 13 lightsticks per km was found at the beaches in the Coqueiros coast. The orange color tubes were taken to the laboratory, where they were opened and used to prepare the stock solution used in the toxicity tests (Cesar-Ribeiro & Palanch-Hans 2010, Cesar-Ribeiro et al 2017. The immiscible compounds were extracted through the dissolution of 0.1 mL of lightstick fluids in 100 mL of filtered seawater (salinity of 35) with ethanol 0.5% (v/v) as a solvent [stock solution ethanol (SSE 0.1%)].…”
Section: Methodsmentioning
confidence: 99%
“…In Brazil, the international non-governmental organization (NGO) Global Garbage executed significant efforts to assess such a problem by collecting and identifying marine litter in beaches from Bahia State (Cesar-Ribeiro & Palanch-Hans 2010, Cesar-Ribeiro et al 2017. As a result, it was possible to identify various debris strongly related to marine vessels as the primary garbage source, potentially harmful to aquatic organisms as the lightsticks, the target object in this study.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations